Efficacy of Anlotinib for the Treatment of Angiosarcoma of the Face and Neck: A Case Report - Ren, Biyong; Wang, Wei; Tan, Jing; Yuan, Bo; Chen, Guilan; Mo, Xiaofei; Fan, Jieqiong; Yang, Bo; Huang, Xiaoping (Frontiers in Oncology, 2021)
Angiosarcoma of the face and neck is a rare soft tissue sarcoma with a high degree of malignancy. The current treatment methods mainly rely on a combination of surgery and radiotherapy and/or chemotherapy. However, the options for drug treatment are very limited and surgery can be difficult to carry out due to the location of the tumor, so the efficacy of first-line drugs needs to be constantly explored. A case of angiosarcoma of the head and face diagnosed by biopsy is reported here. The patient received an oral anlotinib hydrochloride capsule once a day (12 mg on days 1 - 14 / 1 week off for a 21-day cycle) due to the difficulty of surgery. Until now (April, 2020), after 10 months of treatment, the patient's scalp and facial lesions have gradually reduced and the partial response and progression-free survival of this patient were good, with moderate or tolerable adverse events. This approach provides a new approach for the clinical treatment of malignant angiosarcoma of the face and neck with anlotinib as first-line therapy.